Correlates of Suicidality Among A Community-Based Cohort of Women Sex Workers: The Protective Effect of Social Cohesion - Argento, Elena (Journal of interpersonal violence, 2021)
Suicide is a critical public health concern globally. Sex workers experience a disproportionate burden of social and health inequities driven by forms of violence, stigma, and criminalization, yet empirical research on suicidality is limited. This study longitudinally investigated the burden and socio-structural correlates of recent suicidality among women sex workers in Vancouver, Canada. Data (2010-2017) were drawn from a community-based, prospective cohort of cis and trans women sex workers across Metro Vancouver. Women completed biannual interviewer-administered questionnaires, and correlates of suicidality in the last 6 months were analyzed using bivariate and multivariable logistic regression with generalized estimating equations (GEE). Of 867 women at baseline, 48% (n = 413) reported lifetime suicidality, 16% (n = 141) reported suicidality in the last 6 months, and 29% reported suicidality at some point during the study. In multivariable analysis, factors independently associated with suicidality included physical/sexual childhood abuse (adjusted odds ratio [AOR]: 2.99; 95% confidence interval [CI] = [1.75, 5.10]), mental health issues (depression/anxiety/posttraumatic stress disorder; AOR = 2.19; 95% CI = [1.63, 2.95]), intimate partner violence (AOR: 2.11; 95% CI = [1.60, 2.80]), physical/sexual client violence (AOR: 1.82; 95% CI = [1.33, 2.50]), and homelessness (AOR: 1.44; 95% CI = [1.10, 1.89]). Older age (AOR: 0.97; 95% CI = [0.95, 0.99]) and higher social cohesion (AOR: 0.88; 95% CI = [0.78, 0.99]) were significantly associated with reduced odds of suicidality. Findings reveal key socio-structural correlates of suicidality among sex workers including experiences of historical and interpersonal violence, trauma/mental health issues, and homelessness. Strengthening social cohesion may have a protective effect on suicidality. Trauma-informed community-led structural interventions tailored to sex workers are urgently needed alongside a legal framework that enables collectivization and connectedness.